Electrochemical capacitive properties of CNT fibers spun from vertically aligned CNT arrays - Sun, Gengzhi (2013)
Due to their lightweight, large surface area; excellent electrical conductivity; and mechanical strength, carbon nanotube (CNT) fibers show great potentials in serving as both electrode materials and current collectors in supercapacitors. In this paper, the capacitive properties of both as-spun CNT fibers and electrochemically activated CNT fibers have been investigated using cyclic voltammetry and electrochemical impedance spectroscopy. It is found that the as-spun CNT fibers exhibit a very low specific capacitance of 2.6 F g−1, but electrochemically activated CNT fibers show considerably improved specific capacitance. The electrochemical activation has been realized by cyclic scanning in a wide potential window. Different electrolytes have also been examined to validate the applicability of our carbon materials and the activation mechanism. It is believed that such an activation process can significantly improve the surface wetting of the CNT fibers by electrolyte (aqueous Na2SO4 solution). The cycling stability and rate-dependence of the capacitance have been studied, and the results suggest practical applications of CNT fibers in electrochemical supercapacitors.